Taxonomy of the bivalve Ptychomya in the Lower Cretaceous of the Neuquén basin (west‐central Argentina). (31st January 2017) - Milla Carmona, Pablo S.; Lazo, Darío G.; Soto, Ignacio M.
Abstract: In the Lower Cretaceous Agrio Formation, Neuquén Basin (west‐central Argentina), the highly variable genus Ptychomya Agassiz has challenged traditional taxonomists for over a century. Here we apply a previously outlined quantitative protocol in order to settle the taxonomy of the genus based on specimens recorded from the base to the top of the Agrio Formation. The shell outline and ribbing pattern, two prominent external features of the valves, were quantified using geometric morphometric measurements of closed and open outlines, respectively. Morphological groupings were identified using model‐based clustering, and the presence of significant morphological gaps between them was statistically tested. Our results show that the variation historically attributed to a single species, namely Ptychomya koeneni Behrendsen, corresponds to intra‐ and interspecific variability of at least four species, one of which was previously unknown ( Ptychomya esbelta sp. nov.) whereas another was regarded as a subspecies of P. koeneni, namely Ptychomya windhauseni Weaver. We were also able to confirm the specific rank of Ptychomya coihuicoensis Weaver and the presence of P. koeneni in the upper Hauterivian of the Agrio Formation. This study represents a significant improvement over the previous state of knowledge of the genus Ptychomya in the Andes of Argentina, enhancing its biostratigraphical usefulness and palaeobiogeographical significance, and may serve as a model for the study of other poorly known bivalve faunas from other Andean basins of South America.